The role of causality orientations on the motivation and career choices of South African professional musicians, during their formative years - Du Plessis-Kannemeyer, Christina Maria (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMus)--Stellenbosch University, 2023.